Adaptive capacity of coastal community to food insecurity due to climate change-a case of village in West Java - K. Panjaitan, Nurmala; Adriana, Galuh; Virianita, Ratri; Karlita, Nanda; Intan Cahyani, Renita (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTClimate change provokes various problems on coastal community’s life such as reduction in the quantity and quality of the catch, sea-water flood, storms, tidal waves, and drought. Many impacts of climate change will not lead to the vulnerability of coastal communities when a community has sufficient adaptive capacity. The purpose of this study was to analyze the adaptive capacity of coastal communities to food insecurity as the impacts of climate change. Mix method approach such as survey, in-depth interviews, focus group discussions and observation was applied to collect the data. The unit analysis was community level (n = 100 poor fishery households, beneficiaries of government’s poor rice program). The adaptive capacity of communities to food insecurity is relatively low due to low institutional memory, unable to conduct innovative learning and especially the lack of connectedness with others outside the community. There is no Collective action to cope with food insecurity due to poverty, community’s culture and lack of local leadership.Keywords: Climate change, adaptive capacity, coastal community, food insecurityABSTRAKPerubahan iklim menimbulkan banyak masalah pada kehidupan komunitas pesisir seperti penurunan kualitas dan kuantitas tangkapan, rob, badai, gelombang pasang dan kekeringan. Berbagai dampak perubahan iklim tidak akan menyebabkan kerentanan komunitas pesisir bila komunitas itu mempunya kapasitas adaptasi yang memadai. Tujuan penelitian ini adalah menganalisa kapasitas adaptasi komunitas nelayan untuk melihat kesiapan komunitas dalam menghadapi kerawanan pangan akibat perubahan iklim. Pendekatan survei, wawancara mendalam, focus group discussion, dan observasi digunaan untuk mengumpulkan data. Unit analisa adalah pada tingkat masyarakat dengan sumber data 100 rumahtangga nelayan miskin yang merupakan penerima program raskin. Kapasitas adaptasi masyarakat terhadap kerawanan pangan tergolong rendah karena rendahnya institutional memory, tidak mampu melakukan innovative learning dan kurangnya connectedness terutama dengan pihak lain di luar komunitas. Aksi kolektif dari komunitas untuk mengatasi kerawanan pangan tidak ada yang disebabkan oleh kemiskinan,budaya komunitas dan kurang berfungsinya kepemimpinan lokal.Kata kunci: Perubahan iklim, kapasitas adaptasi, pantai komunitas, kerawanan pangan